Effect of flavonoids on remineralization of artificial root caries. (June 2016) - Epasinghe, DJ; Yiu, CKY; Burrow, MF
Abstract: Background: This study compared the effects of three flavonoids, including proanthocyanidin, naringin and quercetin on remineralization of artificial root caries. Methods: Demineralized root fragments (n = 75) were randomly divided into five groups for treatment with the remineralizing agents for 10 minutes: (1) 6.5% proanthocyanidin; (2) 6.5% naringin; (3) 6.5% quercetin; (4) 1000 ppm fluoride; and (5) deionized water (control). The demineralized samples were pH‐cycled through treatment solutions, acidic buffer and neutral buffer for eight days at six cycles per day. The remineralization effects were evaluated using Knoop microhardness, transverse microradiography (lesion depth and mineral loss) and confocal laser scanning microscopy. Microhardness at different lesion depths was analysed with two‐way ANOVA and Tukey's test, while lesion depths and mineral loss were analysed with one‐way ANOVA and Tukey's test. Results: Artificial caries lesions treated with fluoride and flavonoids showed significantly greater hardness than the control group (p < 0.05). Both lesion depths and mineral loss of the flavonoid treated groups were significantly lower than the control group (p < 0.05), but significantly higher than the fluoride treated group. No significant difference in lesion depth and mineral loss was found among the three flavonoids (p > 0.05). Conclusions: All three flavonoids showed positive effects on artificial root caries remineralization, which are significantly lower than that of 1000 ppm fluoride.